Unconscious Human Behaviour in Product Design : Designers ’ Perception , Analysis , and Reflection - Muhammad Jameel, Mohamed Kamil; Shahriman, Zainal Abidin (2014)
The purpose of this paper is to evaluate a new perimeter of design thinking with respect to the value of unconscious human behaviour, as well as the direction for the development of innovative product design. In this study, Verbal Protocol Analysis (VPA) is used as a method to bring out into the open that somewhat mysterious cognitive ability of designers. Designers were asked to sketch a conceptual product design based on given design brief. The design brief consist with four images of interaction between user and products which are categorized into four attributes of unconscious everyday human behaviour. In this session, designers verbalized their thoughts, feelings and beliefs while doing their conceptual sketches. There are two objectives in this study. The first objective of this paper is to find out what words are generally used by designers to describe their perception towards the theory of unconscious human behaviour in product design. The second objective is to determine how designers reflect the theory by generating the innovative concept. This has led to the following implications: